2020
DOI: 10.1111/iju.14170
|View full text |Cite
|
Sign up to set email alerts
|

High performance of 5‐aminolevulinic acid‐induced fluorescent selective upper tract urinary cytology

Abstract: Objectives To investigate the efficacy of selective upper tract urinary cytology using extracorporeal 5‐aminolevulinic acid for the diagnosis of upper urinary tract urothelial carcinoma. Methods We evaluated 104 patients who underwent radical nephroureterectomy and were diagnosed pathologically as having upper urinary tract urothelial carcinoma between March 2013 and May 2019 in Osaka Rosai Hospital. Preoperatively, we collected upper tract urinary cytology from both sides, and compared the sensitivity and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[3][4][5] Yamamichi et al reported the feasibility of selective upper tract urinary cytology by ALA-PDD. 6 The sensitivity and specificity of selective upper urinary cytology were statistically improved by using ALA-PDD. Tumor cells that biologically accumulated protoporphyrin IX in mitochondria show red fluorescence.…”
Section: Editorial Commentmentioning
confidence: 92%
See 1 more Smart Citation
“…[3][4][5] Yamamichi et al reported the feasibility of selective upper tract urinary cytology by ALA-PDD. 6 The sensitivity and specificity of selective upper urinary cytology were statistically improved by using ALA-PDD. Tumor cells that biologically accumulated protoporphyrin IX in mitochondria show red fluorescence.…”
Section: Editorial Commentmentioning
confidence: 92%
“…Yamamichi et al. reported the feasibility of selective upper tract urinary cytology by ALA‐PDD . The sensitivity and specificity of selective upper urinary cytology were statistically improved by using ALA‐PDD.…”
mentioning
confidence: 99%
“…The sensitivity of ALA-induced fluorescence cytology (82%) was higher than conventional cytology (49%) in low-grade tumours and NMIB tumours. Recent studies by Yamamichi et al [69,81] compared 5-ALA guided fluorescent urine cytology to conventional cytology for bladder cancer detection in patient urine samples. They found overall sensitivity and similar specificity rates as the Fujimoto group (5-ALA vs. conventional urine cytology: sensitivity 86.9% to 90.4% vs. 66.3% to 69.4% and specificity 96.2% to 100% vs. 95.6% to 98.2% respectively).…”
Section: -Ala-based Approachesmentioning
confidence: 99%
“…Due to its ability to penetrate the blood brain barrier (BBB), 5-ALA has been used as a contrast probe especially for the visualization of glioma . In recent years, it has also proved effective for urological, endometrial, and gastrointestinal cancers. , 5-ALA hexyl ester, which shows enhanced PpIX production, has been utilized for the detection of bladder cancer . However, the question of whether 5-ALA is able to consistently detect all cancer cells is still under debate.…”
Section: Introductionmentioning
confidence: 99%